2018
DOI: 10.1161/hypertensionaha.117.10510
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 (Toll-Like Receptor 9) Agonist Suppresses Angiogenesis by Differentially Regulating VEGFA (Vascular Endothelial Growth Factor A) and sFLT1 (Soluble Vascular Endothelial Growth Factor Receptor 1) in Preeclampsia

Abstract: Preeclampsia is a common pregnancy-specific disorder characterized by elevated blood pressure and proteinuria. Activation of the maternal immune system and impaired placental angiogenesis are thought to contribute to the pathogenesis of preeclampsia. TLR9 (Toll-like receptor 9) plays a role in innate immunity, defending the organism against infection. The purpose of this study was to determine whether TLR9 inhibits angiogenesis at the fetomaternal interface under conditions of preeclampsia. We confirmed the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 49 publications
7
48
0
Order By: Relevance
“…Cell-free circulating mtDNA (CFCmtDNA) can act as a damage-associated molecular pattern (DAMP) molecule, which elicits an immune response via activation of the pattern recognition receptor, Toll-like receptor-9 (TLR-9) 6 . We and others have previously reported that activation of TLR-9 during pregnancy induced preeclampsia-like signs in rats and mice 10, 11 . In line with these observations, TLR-9 activity was greater in pregnant women with preeclampsia as compared to healthy pregnant women 12 .…”
Section: Introductionmentioning
confidence: 74%
“…Cell-free circulating mtDNA (CFCmtDNA) can act as a damage-associated molecular pattern (DAMP) molecule, which elicits an immune response via activation of the pattern recognition receptor, Toll-like receptor-9 (TLR-9) 6 . We and others have previously reported that activation of TLR-9 during pregnancy induced preeclampsia-like signs in rats and mice 10, 11 . In line with these observations, TLR-9 activity was greater in pregnant women with preeclampsia as compared to healthy pregnant women 12 .…”
Section: Introductionmentioning
confidence: 74%
“…Exciting new work by He et al . has identified an additional role for TLR9 in preeclampsia where they established that TLR9 supressed angiogenesis in part by increasing sFlt-1 expression in a murine model of preeclampsia 27 . Furthermore, research carried out in spontaneous hypertensive rats, illustrated circulating mtDNA may lead to the activation of the innate immune system through TLR9 21 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that expression levels of TLR9 and the amount of cffDNA from the placenta were higher in PE patients compared with that in women with normal placenta (NP), and PE-derived cffDNA stimulated levels of inflammatory cytokine, including IL-1β and sEng secretion depend on TLR9 signaling, compared with NP-derived cffDNA (105). Moreover, a synthetic TLR9 ligand activated inflammatory responses including IL-6 secretion together with stimulation of sFlt1 secretion, while inhibition of TLR9 reduced sFlt1 secretion in human trophoblast cells (106). In mice, administration of a TLR9 ligand induces PE-like symptoms, such as hypertension, proteinuria, placental inflammation, and FGR.…”
Section: Extracellular Dna and The Nlrp3 Inflammasome In Pementioning
confidence: 98%